2022
DOI: 10.2196/38332
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Information Sources, Health Literacy, and COVID-19 Knowledge in the COVID-19 Infodemic: Cross-sectional Online Study in Japan

Abstract: Background The COVID-19 pandemic has caused not only a disease epidemic but also an infodemic. Due to the increased use of the internet and social media, along with the development of communication technology, information has spread faster and farther during the COVID-19 infodemic. Moreover, the increased choice of information sources has made it more difficult to make sound decisions regarding information. Although social media is the most common source of misinformation, other forms of media can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Most of the people could benefit from the number of information sources used [ 39 , 40 , 41 ] when finding health information and making health decisions. Moreover, access to information from interpersonal communication [ 42 ] and mass communication [ 43 , 44 ] can contribute to improving health literacy. Our current study tries to confirm this view, and determine whether health information sources could influence health literacy among older adults in the urban areas of Western China.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the people could benefit from the number of information sources used [ 39 , 40 , 41 ] when finding health information and making health decisions. Moreover, access to information from interpersonal communication [ 42 ] and mass communication [ 43 , 44 ] can contribute to improving health literacy. Our current study tries to confirm this view, and determine whether health information sources could influence health literacy among older adults in the urban areas of Western China.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of infectious disease outbreaks, these reasoning processes may enhance individuals' disease knowledge and improve recognition of symptoms, understanding of the causes and perception of disease risks. Supporting this suggestion, previous research on the COVID-19 pandemic found that interpersonal communication was effective in improving knowledge about the pandemic (Ezeah et al, 2020;Inoue et al, 2022). A study of MERS revealed that the more people expressed MERS-related information on social media, the more they perceived that they were fully informed about MERS (Yoo et al, 2016).…”
Section: Effects Of Interpersonal Communication and Social Media Expr...mentioning
confidence: 78%
“…One of the differences between younger and older adults is that social media use is higher among the younger age groups. Our contemporaneous study found that social media use was higher among those in their 20s and 30s than among the 50s and older age groups [ 36 ]. During the COVID-19 infodemics, high health literacy and correct knowledge may have been more important because a lot of misinformation was disseminated on SNS.…”
Section: Discussionmentioning
confidence: 99%